PENERAPAN PEMBELAJARAN METAPHORICAL THINKING PADA SISWA SMP - Fitriani Fitriani (MEGA: Jurnal Pendidikan Matematika, 2020)
This study was designed to describe the application of mathematics learning with metaphorical thinking in junior high school students. Mathematical learning with metaphorical thinking consists of six learning steps, namely foundation, connecting, compressed conflict, direct analogy, producing analogies, and applications. This research is a quasi-experimental study. The population of this research is all eighth grade students of SMP Negeri 15 Yogyakarta consisting of ten classes. Data collection techniques in this study is a test. The data in this study used a proportion test and paired sample tests with normal approximations. The results obtained are the method of learning mathematics with effective metaphorical thinking in junior high school students.